1974
DOI: 10.1104/pp.53.1.91
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Charge as a Requirement for Axis Elongation in Response to Gibberellic Acid and Kinetin during Stratification of Acer saccharum Seeds

Abstract: The growth potential of embryonic axes of Acer saccharum Marsh. increased during moist storage at 5 C but not at 20 C. During the period of increasing growth potential, the oxygen consumption of the axes remained constant. It was possible to distinguish three phases of the stratification-germination process at 5 C with respect to response of the axis to gibberellic acid and kinetin. From 0 to 10 days the growth regulators had no effect on elongation; from 10 to 60 days axis elongation was stimulated; and betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 20 publications
0
11
2
Order By: Relevance
“…Dormant sugar maple seeds imbibed at 20°C showed a decline in respiration and ATP levels, but only after a prolonged period of 10 to 22 d (20). While our results do not explain what processes occur during stratification which allow sugar pine seeds to move out of a dormant condition into a growing one, they provide a possible explanation as to why dormant sugar pine seeds are unable to germinate at warmer temperatures.…”
contrasting
confidence: 45%
“…Dormant sugar maple seeds imbibed at 20°C showed a decline in respiration and ATP levels, but only after a prolonged period of 10 to 22 d (20). While our results do not explain what processes occur during stratification which allow sugar pine seeds to move out of a dormant condition into a growing one, they provide a possible explanation as to why dormant sugar pine seeds are unable to germinate at warmer temperatures.…”
contrasting
confidence: 45%
“…These findings coincide with those of other previous studies McCarragher et al, 2011), who found little (<3%) or no seeds germinating beyond this temperature. At these warmer temperatures, the level of inhibitors remains high and restricts the Sugar maple germination and climate warming 159 morphological and anatomical changes required for embryonic axis growth, thus reducing the likelihood of germination (Simmonds and Dumbroff, 1974). Increased seed respiration rates also occur, which have been shown to be responsible for loss of seed viability at higher temperatures (Simmonds and Dumbroff, 1974).…”
Section: Effects Of Constant Incubation Temperaturementioning
confidence: 99%
“…While in this study we did perform pre-incubation treatments as a means of getting seeds to germinate uniformly (at least in terms of a starting point) (Janerette, 1978a), our study reinforces the fact that slight variations/abnormalities within the seed and seed structures of the same species may exist. As pointed out by Simmonds and Dumbroff (1974), lower incubation temperatures help facilitate the production of gibberellins, cytokinins and the removal of inhibitors (abscisic and phenolic acids) in sugar maple seeds (Enu-Kwesi and Dumbroff, 1980). Attaining a full energy charge necessary for normal cellular function also occurs at lower temperatures, and could become limited if temperatures are too high.…”
Section: Germination Timingmentioning
confidence: 99%
See 2 more Smart Citations